The use of wiki in teaching and learning Greek a second language for specific academic purposes: challenges and future perspectives - Papadima-Sophocleous, Salomi; Parmaxi, Antigoni (My University, 2012)
Various studies report that incorporating wilds in language courses is a useful and innovative way of enriching the learning environment of students. This qualitative study explores how wikis were used as an integral part of the learning process throughout an intensive Greek course for specific academic purposes. Data was collected through various sources which reported the challenges faced by both the students and the instructor. The findings of this qualitative research suggest that through the use of wilds, the instructor and students met the challenges of: (a) teaching and learning Greek; (b) facilitating and developing digital literacy; and, (c) facilitating students' transition into a new cultural, educational and social environment. The paper concludes with some wiki use perspectives that could be further explored.
Keywords: Greek as a second language for specific academic purposes; Wiki; ICT; Literacy; Social; Educational; Cultural transition